EPR studies of the triangular-lattice antiferromagnet Cs2CuBr4 - Schulze, E.; Ponomaryov, A.N.; Wosnitza, J.; Tanaka, H.; Zvyagin, S.A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2019)
The spin dynamics of the spin-1/2 triangular-lattice antiferromagnet Cs2CuBr4 is probed by means of high-frequency electron paramagnetic resonance (EPR) spectroscopy. Temperature dependences of EPR parameters are studied in a broad temperature range between 1.4 and 200 K for different orientations of the applied magnetic field. In the high-temperature regime (T >> J/kB), an unusually broad and anisotropic resonance line is detected, suggesting a sizeable Dzyaloshinskii–Moriya interaction. Employing the theory of exchange narrowing, the ratio of the Dzyaloshinskii–Moriya vector components, Dc/Da ≈ 0.3, is estimated.